Dissipation of seabird‐derived nutrients in a terrestrial insular trophic web. (27th May 2022) - Gaiotto, Juliana Vallim; Nunes, Guilherme Tavares; Bugoni, Leandro
Abstract: Highly mobile organisms can transport nutrients and energy among distinct ecosystems, such as between oceanic foraging areas and terrestrial breeding sites. Seabirds are great nutrient carriers and potentially play a key role in the maintenance of trophic webs on islands. In this study, we assessed three dimensions of marine nutrient dissipation—horizontal, temporal and vertical—on the tropical Meio Island of Fernando de Noronha Archipelago, Brazil. For this, C3 and C4 plants, ants and spiders found in a 100 m long transect between colonies of masked ( Sula dactylatra ) and red‐footed boobies ( Sula sula ) were sampled during the rainy (the masked booby breeding period) and dry seasons (the red‐footed booby breeding period). The marine contribution to the terrestrial trophic web was analysed using Bayesian mixing models from a carbon and nitrogen stable isotope data set. The main findings indicate that marine nutrients in the terrestrial trophic web dissipated horizontally as the distance from the colony increased, which was more marked during the rainy season. On the vertical axis, the relative contribution of marine nutrients in terrestrial consumers was strongly related to food habits but not necessarily to the trophic level, dissipating rather than increasing, due to variable omnivory and the use of terrestrial food sources. The breeding strategy of the masked booby (i.e. incubating eggs on the ground), in addition to a larger body size and larger colony, could produce a more concentrated pulse of nutrients in comparison to seabirds nesting sparsely on trees, contributing more efficiently to the enrichment of marine nutrients on land. The importance of seabirds for the maintenance of interconnected ecosystems has been demonstrated, and the role of marine‐derived nutrients in the enrichment of nutrient‐poor tropical islands.